Digital Community Engagement Partnering Communities with the Academy - Heppler, Jason; Wingo, Rebecca; Schadewald, Paul (University of Cincinnati Press, 2020)
How have university scholars across a variety of disciplines navigated the co-creative and collaborative relationships involving community partners? How has the addition of digital components changed the way information can be communicated to the intended audience? Through digital projects, traditional academic silos have given way to community-based partnerships which open research, storytelling, and curation to wide array of contributors from civic engagement professionals, librarians, archivists, technology personnel, local citizens, and academics. The collaborative process may push your comfort zone and make you grapple with your roll of storytelling but as the authors of the last chapter say, "You can't make ketchup without smashing a few tomatoes." Digital projects can empower communities through collaboration and create new primary sources, collapse barriers, and spark new dialogue. Digital Community Engagement "lifts the hood" and presents nine examples of digital collaborations from constructing a public response to police violence, to creating digital stories of homelessness, to young activists united around local people in the Deep South to build a grassroots movement for social change. Wingo, Heppler and Schadewald bring together cutting-edge campus-community partnerships with a focus on digital projects. The case studies, authored by academics and their community partners, explore models for digital community engagement that leverage new media through reciprocal partnerships. The contributions to this volume stand at the crossroads of digital humanities, public history, and community